KYAI'S LEADERSHIP IN BUILDING RELIGIOUS MODERATION IN PESANTREN-BASED UNIVERSITIES: A MULTICULTURAL PERSPECTIVE - Fajar, Muhammad Sahal Malik (Nurul Jadid University, Paiton Probolinggo, East Java, 2024)
The purpose of this research is to shed light on the leadership dynamics within Islamic boarding schools-based universities, mainly focusing on the role of Kyai in promoting religious moderation. By understanding the strategies and approaches employed by Kyai, this study aims to contribute to the discourse on religious leadership and multicultural education within the Islamic context. Through a qualitative approach utilizing a case study methodology, the research delves into the nuanced practices of Kyai within selected institutions. Findings illuminate Kyai's multifaceted contributions: firstly, as a revered role model embodying moderation, tolerance, and inclusivity; secondly, as a religious facilitator providing guidance and interpretation promoting interfaith understanding; and finally, as architects of a conducive learning environment where diverse perspectives are respected and dialogue flourishes. This research underscores Kyai's significance in nurturing religious moderation and advancing multiculturalism within Islamic educational contexts, offering valuable insights into effective leadership strategies for fostering tolerance and understanding in higher education settings.